(untitled) (Materiali di Estetica. Terza serie, 2022)
The article offers an excursus on with some debates related to the world of architecture and urban planning. The traces of a “school of Milan” are manifested in a thought that understands the city not as a place of economic speculation but as a territory for human expression, as the words of Ernesto Treccani recall